Upaya Guru PPKn Dalam Mengatasi Kenakalan Remaja Di Kelas X SMK Sunan Bonang Maron - Shinta Bella; Nurul Saila; Ani Sulianti (Jurnal Pendidikan Sosial Dan Konseling, 2024)
PPKn teachers at the Sunan Bonang Vocational School are required to be able to make efforts to overcome cases of juvenile delinquency that occur in schools, especially for class X, this is an additional task for PPKn teachers. The principal of Sunan Bonang Vocational School gave full authority to PPKn teachers to deal with cases of juvenile delinquency that occurred, this was due to the absence of a guidance counselor. The aim of this research is to find out the various cases of juvenile delinquency that occur in class Bonang Maron. The research method used is a descriptive qualitative approach. The research location chosen was Sunan Bonang Maron Vocational School, Probolinggo Regency. The sources used are the main data source and additional data sources. Data collection techniques used by researchers include: observation, interviews, and documentation. The data analysis technique involves reflecting on the results of observations which will later be analyzed using qualitative analysis. Meanwhile, checking the validity of the data uses triagulation techniques. The results of the research show that there are many cases of juvenile delinquency in class behind the school, damaging classroom facilities. The causal factors are divided into 2, namely : (1) factors from within the student himself such as very high curiosity, being raised in a disharmonious family and (2) external factors such as the influence of friends, inheritance of negative behavior from his seniors. The efforts made by PPKn teachers in dealing with cases of juvenile delinquency in class : (1) efforts before cases of juvenile delinquency occur, (2) efforts after cases of juvenile delinquency, (3) healing efforts after cases of delinquency. The inhibiting factors for PPKn teachers in dealing with cases of juvenile delinquency include: (1) lack of parental attention, (2) unhealthy social environment, (3) student indifferent attitude towards teacher advice.